PENGEMBANGAN HASIL PRODUKSI OLEH-OLEH TERHADAP PENINGKATAN PENDAPATAN UMKM DI KOTA BATU, MALANG - RIFAYANTI RIFAYANTI; GIFA RAHMA; NURUL AULIA; Nuraisyah Nuraisyah; Salingkat, Syarif Permana; Gita Farista (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of micro, small, and medium enterprises (MSMEs) in tourism areas plays a vital role in improving local economic growth, particularly through the production of regional souvenirs. This study aims to analyze how product development contributes to increasing MSME income in Batu City, Malang. Using a qualitative descriptive approach, data were collected through in-depth interviews, participant observation, and documentation involving souvenir MSME actors around Batu City Square. The findings show that product innovation—such as improving raw material quality, adding product variations, and enhancing packaging design—significantly increases consumer interest and purchasing power. Attractive and symbolic packaging also allows MSMEs to increase selling prices while maintaining demand. Additionally, expanded marketing networks strengthen sales performance. Overall, product development is proven to be a key strategy for increasing MSME income and supporting sustainable tourism-based creative economic growth in Batu City.